PERWATAKAN TOKOH DALAM NOVEL GENDUK KARYA SUNDARI MARDJUKI - Yuliana, Yuliana; Salem, Laurensius; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study describes the problem, while this research is useful for researchers to increase knowledge and insight in analyzing the works of literature, can be used by teachers and students as a medium of learning and as a comparison material for other research. "How does a character figure in Genduk novel by Sundari Mardjuki ? The method used in this research is descriptive method. The reason for choosing the deskrptif method because this research is to describe and describe the character figures contained in Genduk novel. Descriptive method is a method that expresses, describes, describes, describes, and exposes the object. Data collecting technique used in this research is documentary study. This datorenter study is done by reviewing sentences or quotations of figures and figures who became the source of. Thus the author himself as a key instrument as a planner, meaning the researcher is located as planner, executor, data collector, analyzer, data interpreter, and ultimately the research rapporteur. After the data is analyzed to be tested its validity first, it is intended that the researchers get an objective result. To get the data validity, there are four ways to use as follows :Reference Sufficiency, peer examination, triagulation, and observational perseverance.      Keywords:characterization, psychology, novel